Meeting The Mentorship Needs Of International Students In The United States - Oluyomi Oloruntoba; Roaa Aggad; Tasmiah Nuzhath; Qiping Fan; Matthew Lee Smith (New Prairie Press, 2022)
Mentorship of international students is an enriching experience because international students studying in the United States enhance inclusion and diversity within the university environment by contributing their unique cultural and societal experiences and perspectives. International students have unique needs regardless of their country of origin and exposure. This paper provides the perspectives of international students on recommendations and strategies that mentors could employ to meet some of the identified needs of international students.